2018
DOI: 10.1371/journal.pone.0189954
|View full text |Cite
|
Sign up to set email alerts
|

International migration patterns of Red-throated Loons (Gavia stellata) from four breeding populations in Alaska

Abstract: Identifying post-breeding migration and wintering distributions of migratory birds is important for understanding factors that may drive population dynamics. Red-throated Loons (Gavia stellata) are widely distributed across Alaska and currently have varying population trends, including some populations with recent periods of decline. To investigate population differentiation and the location of migration pathways and wintering areas, which may inform population trend patterns, we used satellite transmitters (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Red-throated divers are medium sized birds with weight varying between 1400g -2000g (own observations), and with high wing loading (Storer 1958;Lovvorn and Jones 1994). Despite this, these birds often need to cover long distances to their breeding grounds (www.divertracking.com;McCloskey et al 2018), with some individuals travelling as far as 850km or 1300km in a single flight (Kleinschmidt et al unpubl data). Weber et al (1997) Diet composition of red-throated divers in the German Bight showed the importance of resting sites for refuelling.…”
mentioning
confidence: 99%
“…Red-throated divers are medium sized birds with weight varying between 1400g -2000g (own observations), and with high wing loading (Storer 1958;Lovvorn and Jones 1994). Despite this, these birds often need to cover long distances to their breeding grounds (www.divertracking.com;McCloskey et al 2018), with some individuals travelling as far as 850km or 1300km in a single flight (Kleinschmidt et al unpubl data). Weber et al (1997) Diet composition of red-throated divers in the German Bight showed the importance of resting sites for refuelling.…”
mentioning
confidence: 99%
“…In the Baltic Sea, northern Europe, an important overwintering habitat of aquatic birds, there was an 85% reduction of Red-throated Loon and Arctic Loon (Gavia arctica) from 1987 to 2000 (Skov et al 2011), declines generally considered to originate from increased mortality in marine habitats (Schmutz 2014), but also from ecological disturbance to nesting ponds in Swedish populations (Eriksson 1994). Red-throated Loon from Haida Gwaii are thought to overwinter on inshore marine waters in southern British Columbia (Campbell et al 1990) and possibly further south, as recent satellite-tracking of Alaskan birds (McCloskey et al 2018) indicates that some adults overwinter in coastal waters of Mexico. Inshore habitats impose the highest risk to overwintering seabirds (Croxall et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…After nearly a century of telemetry innovation, there is now a wide array of telemetry devices with an even wider array of potential applications [1,2,12,16]. Telemetry now enables studies on topics such as animal movement and migration [17][18][19], physiological processes [20,21], or social interactions [22], and our survey respondents compiled an even longer list of current applications (Additional file 2). However, the survey responses also show how many research interests still cannot yet be satisfactorily investigated using telemetry.…”
Section: Technological Trade-offsmentioning
confidence: 99%